PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN GAYA BELAJAR MAHASISWA TERHADAP HASIL BELAJAR MATA KULIAH WIRASWASTA (STUDI KUASI-EKSPERIMEN PADA MAHASISWA TINGKAT II AKADEMI REFRAKSI OPTISI KARTIKA INDERA PERSADA TAHUN AKADEMIK 2025/2026) - Sahel Sahel; Ebtaria Hartiwi Putri; Suci Haryanti; Atti Kartikawati; Fitri Yati; Shinta Amelia Astuti (Journal of Innovation Research and Knowledge, 2026)
This study aims to analyze the effect of Problem Based Learning (PBL) on student academic achievement in the Entrepreneurship course at Akademi Refraksi Optisi Kartika Indera Persada for Academic Year 2025/2026, considering learning style as a moderating variable. A quantitative quasi-experimental nonequivalent control group design was employed, involving the Regular Class (Semester IV) as the experimental group (n=27) implementing PBL and the GW Class (Semester III) as the control group (n=23) receiving conventional instruction. Learning outcomes were measured using a weighted final score comprising Attendance (15%), Project (10%), Quiz (5%), Assignment (10%), Midterm Exam/UTS (20%), and Final Exam/UAS (40%). Data were analyzed through descriptive statistics, Shapiro-Wilk normality test, Levene's homogeneity test, and Mann-Whitney U test. Descriptive results showed mean final scores of 80.15 (SD=2.66) for the experimental class and 80.43 (SD=1.53) for the control class. Component-level analysis revealed significant differences in most individual components, with the experimental class outperforming in Project, Quiz, Assignment, UTS, and UAS, while the control class had higher attendance. Shapiro-Wilk confirmed non-normal distribution in both classes (p<0.05), and Levene's Test indicated heterogeneous variances (F=4.146, p=0.047). The Mann-Whitney U test yielded U=316.00 with p=0.911 (p>0.05), confirming H0: no statistically significant difference in aggregated final scores. Pedagogical implications and recommendations for future research are discussed.